2011
DOI: 10.1093/bja/aeq335
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of nonogenarians undergoing emergency, non-trauma surgery

Abstract: The study gave scientific support and actual figures to many intuitive beliefs: morbidity and mortality are high and are associated with many preoperative comorbidities. All this, combined with an already reduced life expectancy, and a presumably low physiological reserve makes these patients particularly vulnerable to emergency surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
5
12
1
Order By: Relevance
“…There are relatively few studies regarding the results of gastrointestinal surgery in nonagenarians . The mortality obtained in our series, 28.9%, is within the range published in the literature, which includes figures as high as 55.0% . In a review carried out by Rivoirard et al ., operative mortality oscillated between 9.4% and 24.0% .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…There are relatively few studies regarding the results of gastrointestinal surgery in nonagenarians . The mortality obtained in our series, 28.9%, is within the range published in the literature, which includes figures as high as 55.0% . In a review carried out by Rivoirard et al ., operative mortality oscillated between 9.4% and 24.0% .…”
Section: Discussionsupporting
confidence: 75%
“…It is applicable from the preoperative period, and has also been validated as a predictor of morbidity, mortality and length of hospital stay, besides assisting decision‐making in the operating room . Several studies, as in our case, have observed a strong association between ASA‐PS and perioperative mortality in nonagenarians . In the present series, as the ASA‐PS score increased, the percentage of deaths also grew, escalating from a mortality of 11.5% in ASA II patients to a mortality of 37.5% in ASA IV patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the literature consulted, the mortality of elective surgery in this age group ranged from 4% to 20% . For emergency surgery, this ranged from 19% to 54.9% . In our case the figure was 37.6%, which we relate to the lack of patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, according to the Italian National Institute for Statistics (Istituto Nazionale di Statistica, ISTAT), there were approximately 13.5 million people aged 65 and older in 2016, representing 22.3% of inhabitants [3,4], and this value will continue to grow in the following years. Recovery, particularly for surgical emergencies, is considered complicated in the elderly [5][6][7], who tend to have longer hospital stays [7][8][9] (this is related to comorbidities, an elevated number of drugs taken, and reduced physical and mental reserves) [3,5,8,9]. Not all patients of the same age have the same risks or frailty issues (in Surgeries 2021, 2 120 multiple physiological systems, this is defined as age-related cumulative decline, and is considered a better predictor of mortality and morbidity than chronological age in the elderly).…”
Section: Aimmentioning
confidence: 99%